Fusarium Species and Fusarium oxysporum Species Complex Genotypes Associated With Yam Wilt in South-Central China - Dongzhen, Fang; Xilin, Liu; Xiaorong, Chen; Wenwu, Yan; Yunlu, He; Yi, Cheng; Jia, Chen; Zhimin, Li; Litao, Guo; Tuhong, Wang; Xu, Jianping; Chunsheng, Gao (Frontiers in Microbiology, 2020)
Chinese yam (Dioscorea polystachya Thunb.) is an important root crop. Wilt caused by Fusarium is among the most important emerging diseases on yams. However, there is currently limited information on the molecular epidemiology of Fusarium causing yam wilt. Here, we investigated wilted yam samples from six regions in South-Central China. A total of 117 Fusarium isolates were obtained from diseased tissues of 37 wilted yam plants. These yam plants belonged to two varieties characterized by white and purple fleshy tubers respectively. Analyses of ef1- sequences identified that these 117 Fusarium isolates belonged to 11 putative species, with F. aff. commune being the most common (31.6%), followed by F. aff. cugenangense (29.1%), a potential undescribed species Fusarium aff. sp. (11.1%), F. aff. gossypinum (9.4%), F. aff. fujikuroi (8.5%), F. aff. nirenbergiae (6%), and one isolate each (0.85%) of F. aff. asiaticum, F. aff. curvatum, F. aff. odoratissimum, F. aff. solani, and F. aff. verticillioides. Six of these species were recently described as new species within the Fusarium oxysporum species complex (FOSC). Interestingly, 18 of the 37 yam plants were infected by two or more Fusarium species each and there was evidence for differential Fusarium species distributions based on geographic location and/or yam host variety. Multilocus microsatellite genotyping of the 67 FOSC isolates revealed that isolates of the same species from the same diseased plants often belonged to different genotypes. Interestingly, several FOSC microsatellite genotypes were shared among distinct geographic regions, consistent with long-distance dispersal. However, population genetic analyses revealed significant contributions of geographic separation to the overall genetic variation of FOSC with several pairs of geographic populations showing significant genetic differentiations, consistent with differential geographic distribution of the species within FOSC. The implications of our results to the managements of Fusarium wilt in yams were discussed.